Understanding Landscape Multifunctionality in a Post-forest Frontier: Supply and Demand of Ecosystem Services in Eastern Amazonia - Pinillos, Daniel; Bianchi, Felix J. J. A.; Poccard-Chapuis, Rene; Corbeels, Marc; Tittonell, Pablo; Schulte, Rogier P. O. (Frontiers in Environmental Science, 2020)
Sustainable food production requires approaches that reconcile agricultural production with the conservation and sustainable use of natural resources, biodiversity and associated ecosystem services. While the contribution of agriculture to the provision of individual ecosystem services has received considerable scientific attention, little is known about the extent to which tropical landscapes can meet societal expectations related to food production and environmental sustainability simultaneously. We assessed how the spatial configuration of pedo-morphology and land uses influences the provision of three soil-based ecosystem services in eastern Amazonia: carbon storage (CS), habitat for biodiversity (HB) and agricultural commodity production (CP). We use the Functional Land Management framework to assess the supply and demand of these ecosystem services in a spatially explicit manner to identify areas of (mis)matches and trade-offs in the municipality of Paragominas, Brazil. The supply of ecosystem services was informed by a literature review for the various combinations of pedo-morphological characteristics and land uses in the region. The demand for ecosystem services was mapped based on federal and state policy targets. Mapping the supply and demand of CS indicated that half of the carbon in the region is stored in remnants of undisturbed forest which cover only a third of the municipality. Demand for HB in terms of forested area is met but it does not guarantee safeguarding biodiversity. Roughly a third of the territory shows scarce quality of HB even when compliant with legislation. Concerning CP, we identified areas where both supply and the demand to increase production are relative high due to road access and lower intensification costs. The demand for agricultural production can eventually incentivize the expansion of agriculture on fertile soils, which could compromise environmental targets. Our results suggest that the simultaneous delivery of multiple ecosystem services may require land-use pathways that combine land sparing and sharing approaches. Our analysis can inform integrated land-use planning initiatives where, historically, the supply and demand for CP have been the single dominant driver for the current landscape configuration.